603 Workplace practices and policies to prevent msd: developing an implementation guide. (24th April 2018) - Van Eerd, D; Irvin, E; Cullen, K
Abstract : Introduction: Musculoskeletal disorders (MSD) continue to be a major burden for workplaces and workers as well as insurance and health systems. Evidence-based approaches are desired but research-to-practice gaps remain. One reason for gaps is the necessary research of sufficient quality is often not available. However evidence-based practice considers both scientific evidence as well as practitioner expertise. Our objective is to synthesise evidence from the scientific literature, practice evidence (policies and practices), and experiences from stakeholders. Methods: Scientific evidence from recently published reviews, including a recent review our team completed, will be synthesised. Evidence from practitioners' expertise and worker experiences are being collected using a web-based survey, focus groups, and interviews with representatives from various stakeholder groups from multiple sectors. We are using the Public Health Agency of Canada's best practices portal to structure data collection of workplace practices and policies. We are synthesising the evidence gathered from stakeholders with that from recently published systematic reviews. Result: Recent systematic review results revealed 61 high and medium studies addressing MSD. The studies described 30 different intervention categories. There was strong evidence that resistance training has a positive effect and moderate evidence that stretching, using a feedback mouse, and workstation forearm supports have positive effects. However the level of evidence was too low to make recommendations for many other interventions. The survey and interview/focus groups to collect practice-based evidence are ongoing. Discussion: The presentation will focus on current policies and practices described by our practitioner and workplace audiences as compared to the scientific evidence. The discussion will outline the synthesis of evidence and co-creation (with OHS stakeholders) of a practical guide to help workplaces develop and implement effective practices and policies to prevent MSD and help workers with MSD return to work safely.